Sensitive detection of a bacterial pathogen using allosteric probe-initiated catalysis and CRISPR-Cas13a amplification reaction - Jinjin Shen (Nature Portfolio, 2020)
The detection of pathogens in food and clinical samples remains a challenge. Here, Shen et al. present a detection system, involving a combination of nucleic acid-based allosteric probes and CRISPR-Cas13a components, that can detect very low numbers of a bacterial pathogen in milk and serum samples without isolation.